Determination of GT-transition Strengths in \(A=34\) Isobars Using Charge Exchange \((^3\text{He},t)\) Reaction - Khai, Nguyen Tuan; Linh, Bui Duy; Thiep, Tran Duc; Fujita, Y.; Adachi, T; Fujita, H.; Tamii, A. (Communications in Physics, 2012)
Under the assumption that isospin \(T\) is a good quantum number, mirror transitions \(T_{z }= +1 → 0\) and \(T_{z }= -1 → 0\) were studied in \(A = 34\) isobars, where \(T_{z}\) is \(z\) component of iospin \(T\) and is defined by \(T_{z} = (N-Z)/2\). With a high energy resolution of 35 keV in \(^{34}\)S\((^{3}He,t)^{34}\)Cl reaction measurement at \(0^{°}\) scattering angle and at an incident energy of 140 MeV/nucleon, strengths of Fermi and Gamow-Teller (GT) transitions from the \(J^{π } = 0^{ + }\), \(T_{z }= +1\) ground state of \(^{34}\)S to the \(J^{π } = 1^{+ }\), \(T_{z }= 0\) excited states in \(^{34}\)Cl were determined up to excitation energy \((E_{x})\) of \(7.08\) MeV. The corresponding isospin-symmetric transitions connecting \(T_{z }= -1\) and \(T_{z }= 0\) states can be studied in the \(^{34}\)Ar \(β ^{ + }\) decay. The strengths of the \((GT)_{± }\) transitions were compared up to the excitation energy of 3.1 MeV. A good agreement was observed for two strong transitions to \(2.580\) MeV and \(3.129\) MeV states, while a disagreement about \(45\text{%}\) was observed for a weaker transition to \(0.666\) MeV low-lying state.